Pengaruh Profitabilitas dan Struktur Modal Terhadap Return Saham Pada Perusahaan Sektor Infrastruktur di Bursa Efek Indonesia (Periode 2021-2023) - Ismala Dewi; Febrina Rita Albeta (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study was conducted with the aim of determining the effect of profitability represented by Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS) and Capital Structure represented by Debt to Equity Ratio (DER) on Stock Returns in Infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The number of samples in this study were 43 companies with a total of 109 data.  This study uses an associative method with a quantitative approach. The data source used is secondary data. The data analysis method used are descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, and determination coefficient test (R2). The results of this study are that ROA has a positive and significant effect on stock returns. ROE has a positive and significant effect on stock returns. EPS has no effect on stock returns. DER has a negative and significant effect on stock returns